Determining the Cost of Goods Manufactured Using the Order Method at Mami Kue MSME - Nurlela; Kartika, Satria Ayu (Cattleya Darmaya Fortuna, 2025)
Determining the cost of production is very important as a basis for determining the selling price and profit in MSMEs, because knowledge of the cost of production makes it easier for MSME players to determine the selling price and profit of the products sold. The purpose of this study is to determine the calculation of the cost of production using the order method at the Mami Kue MSME for sengkulun cake products for the calculation period of January-March 2025. Data collection techniques used field studies, namely interviews, observations, field notes, and documentation. The type of research data used is primary data. The data analysis method used in this study is quantitative description, which consists of managing data from the production process, including transaction records related to the purchase or procurement of raw materials, auxiliary materials, direct labor costs, and factory overhead costs, presenting the data in a cost of production report that is interpreted in the results and discussion of the study. The results of the calculation of the production cost per unit of sengkulun cake using the order method during January-February 2025 are as follows: January is Rp 1,091, February is Rp 1,105, and March is Rp 1,164. A comparison of the cost of production of sengkulun cakes according to the calculations of Mami Kue MSMEs and according to the order method shows a difference of Rp 208 in January, Rp 206 in February, and Rp 205 in March.